Conditions of Poor Waste Pickers in the Plastic Waste Supply Chain in The Implementation of Circular Economy at Mahija Parahita Nusantara Foundation - Fadilah Yusro Bako; Sari Viciawati Machdum (Cita konsultindo, 2025)
This Research explores the conditions of waste pickers (pemulung) face within the plastic waste supply chain under the circular economy framework in Yayasan Mahija Parahita Nusantara. The research focuses on understanding how waste pickers contribute to circular waste management and how structural poverty affects the waste pickers’ well-being. This research used a qualitative descriptive approach with in-depth interviews, observations and document study with purposely selected informants, including waste pickers, middlemen, and program managers. Findings reveal the community segment as the primary source of household waste; it still lacks consistent waste separation practices, limiting the quality of recyclable input. Waste pickers, in the second segment, face multiple vulnerabilities including lack of legal identity, unstable housing and low bargaining power. Another condition was waste pickers do not have direct access to industry due to limited volume and should pass the long chain through various chains from small traders, medium traders, large traders and industry. Despite their contribution, they remain marginalised, earning only IDR 2500-6500/kg depending on waste conditions. Middlemen dominate the third segment, setting the prices and often benefiting from informal loyalty systems with waste pickers, while gaining significantly higher margins by reselling to large buyers. And the last segment, industry receives to process the plastic but remains disconnected from the social realities of upstream actors. This study highlights the need for a more inclusive business that improves equity and economic justice across all supply chain segments, especially for waste pickers and other informal workers.